2021
DOI: 10.1186/s41155-021-00192-x
|View full text |Cite
|
Sign up to set email alerts
|

The dimensionality of phonological awareness among Brazilian Portuguese-speaking children: a longitudinal study

Abstract: Phonological awareness is one of the most important predictors of reading. However, there is still controversy concerning its dimensionality. This study evaluated the dimensionality of phonological awareness among Brazilian Portuguese-speaking children. A total of 212 children performed six phonological awareness tasks in the last year of kindergarten. Of those children, 177 performed the same tasks when they were in the first grade. The phonological awareness measures differed in both their cognitive demand (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Considering the dimensionality and the developmental facets of phonological awareness in previous research (e.g., Justi et al, 2021), three composite measures of phonological awareness were evaluated: supra-phonemic awareness (sum of scores on supra-phonemic tasks: syllable blending and syllable segmentation); phonemic awareness (sum of scores on phonemic tasks: phoneme blending, phoneme segmentation, and phoneme elision); and total phonological awareness (sum of scores on phonemic and supra-phonemic tasks). These measures were calculated to enable the analysis of the accuracy of the at-risk/not-at-risk classification of reading and writing difficulties by the authors of this research.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the dimensionality and the developmental facets of phonological awareness in previous research (e.g., Justi et al, 2021), three composite measures of phonological awareness were evaluated: supra-phonemic awareness (sum of scores on supra-phonemic tasks: syllable blending and syllable segmentation); phonemic awareness (sum of scores on phonemic tasks: phoneme blending, phoneme segmentation, and phoneme elision); and total phonological awareness (sum of scores on phonemic and supra-phonemic tasks). These measures were calculated to enable the analysis of the accuracy of the at-risk/not-at-risk classification of reading and writing difficulties by the authors of this research.…”
Section: Resultsmentioning
confidence: 99%
“…Phonological awareness has been defined as the ability to discriminate, identify, and manipulate the units of oral language, such as phonemes, onset-rimes, syllables, or words (Bdeir et al, 2022;Herrera et al, 2021;Justi et al, 2021). Thus, it involves phonological sensitivity, but also metalinguistic abilities.…”
Section: Psicología Educativamentioning
confidence: 99%
“…These last types of tasks can be performed for units positioned anywhere within the word (at the beginning, middle, or end of the word). Research has also indicated that syllable, intra-syllable, and phoneme awareness are distinguishable, yet intercorrelated, dimensions of phonological awareness (Defior & Serrano, 2011;Justi et al, 2021;Meira et al, 2019).…”
Section: Psicología Educativamentioning
confidence: 99%
“…Although writing readiness skills have been recognized as a crucial predictor of reading skills (Hammil, 2004), only a limited number of studies have specifically focused on the predictive effect of writing readiness skills. Conversely, numerous studies have examined the predictive effect of reading skills (Gerde, Bingham, & Wasik, 2012;Hooper et al, 2010;Justi, Henriques, & Justi, 2021;Vadasy, Sanders, & Abbott, 2008). These studies have found that certain skills, such as phonological awareness, alphabet knowledge, print awareness, and vocabulary, are predictors of writing skills.…”
Section: Introductionmentioning
confidence: 99%